2021
DOI: 10.1021/jacs.1c08484
|View full text |Cite
|
Sign up to set email alerts
|

Polymers Strive for Accuracy: From Sequence-Defined Polymers to mRNA Vaccines against COVID-19 and Polymers in Nucleic Acid Therapeutics

Abstract: Unquestionably, polymers have influenced the world over the past 100 years. They are now more crucial than ever since the COVID-19 pandemic outbreak. The pandemic paved the way for certain polymers to be in the spotlight, namely sequencedefined polymers such as messenger ribonucleic acid (mRNA), which was the first type of vaccine to be authorized in the U.S. and Europe to protect against the SARS-CoV-2 virus. This rise of mRNA will probably influence scientific research concerning nucleic acids in general and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 184 publications
(327 reference statements)
0
14
0
Order By: Relevance
“…Nucleic acids, such as, DNA, RNA, etc., encoding viral antigens can be delivered by encapsulating them within polymeric nanovesicles which also contributes to their protection from easy degradation often caused by RNases. [ 187 , 188 ] These pioneering studies have demonstrated that the nanovesicular PNCs have the advantages of biocompatibility and biodegradability, size tuning, co‐loading of adjuvants and active agents, colloidal stability, stimuli‐responsive properties, and antigen functionality. Thus, polymeric nanovesicles are one of the potential multi‐stimuli responsive multi‐drug delivery nanocarrier which can become a prominent candidate to advance vaccine research and provide solution to the ongoing pandemic and beyond.…”
Section: Various Polymeric Nanocarriers For Drug Deliverymentioning
confidence: 99%
“…Nucleic acids, such as, DNA, RNA, etc., encoding viral antigens can be delivered by encapsulating them within polymeric nanovesicles which also contributes to their protection from easy degradation often caused by RNases. [ 187 , 188 ] These pioneering studies have demonstrated that the nanovesicular PNCs have the advantages of biocompatibility and biodegradability, size tuning, co‐loading of adjuvants and active agents, colloidal stability, stimuli‐responsive properties, and antigen functionality. Thus, polymeric nanovesicles are one of the potential multi‐stimuli responsive multi‐drug delivery nanocarrier which can become a prominent candidate to advance vaccine research and provide solution to the ongoing pandemic and beyond.…”
Section: Various Polymeric Nanocarriers For Drug Deliverymentioning
confidence: 99%
“…The most significant advantage over LNP polymer nanoparticles is that they are easy to synthesize and can be modified by changing the polymer structure to achieve the goal of improved properties. 113 The following is a survey of the latest PNP research progress.…”
Section: Polymer Nanoparticles (Pnp)mentioning
confidence: 99%
“…Polymer materials for the delivery of mRNA vaccines have been proven to be efficient in preclinical studies [ 95 ]. However, new functional polymers, with improved biodegradability and delivery efficacy, are desirable before the translation of polymer-based mRNA vaccines in the clinic.…”
Section: Delivery Vehiclementioning
confidence: 99%